(untitled) (Journal of Medicine, 2012)
Gitleman syndrome is a rare entity. It is a benign disorder that can present with many metabolic derangements. Here we report a patient presenting with recurrent episodes of muscle weakness, muscle cramps that was diagnosed as a cas of Gitlemans syndrome. DOI: http://dx.doi.org/10.3329/jom.v13i1.10090 JOM 2012; 13(1): 118-119